Fodder productivity and growth persistency of three local cassava varieties - Tung, C.M.; Liang, J.B.; Tan, S.L.; Ong, H.K.; Jelan, Z.A. (Asian-Australasian Association of Animal Production Societies, 2001)
Three cassava varieties, namely MM 92 (MM), Black Twig (BT) and Local (LC), were arranged in a randomized complete block design to evaluate their dry fodder and crude protein (CP) productivity as well as growth persistency. Cassava plants grown in small plots of 5 mx10 m at a planting distance of 25 cmx25 cm were harvested every 6 weeks starting from 3 months after planting. Dry fodder yields of MM, BT and LC over the 8 harvests were 8.55, 8.01 and 6.15 t/ha, respectively. All varieties produced more leaves than stems with average leaf:stem ratios of 5, 5.9 and 4.8 for MM, BT and LC, respectively. In terms of CP production, MM was the highest yielder (272 kg/ha/harvest), followed by BT and LC (238 and 184 kg/ha/harvest, respectively). The total accumulative CP amounts over the 8 harvests were 2179, 1903 and 1474 kg/ha for MM, BT and LC, respectively. The mortality rates were 9.91, 14.01 and 13.98% for MM, BT and LC, respectively. Phosphorus content was more stable than potassium content during defoliation. MM, BT and LC had whole plant phosphorus contents of 0.41, 0.41 and 0.39%, respectively; whole plant potassium contents were 1.25, 138 and 1.20%.